Harnessing the opportunities of inclusive technologies in a global economy - Gustavo Beliz; Ana Inés Basco; Belisario de Azevedo (Kiel Institute for the World Economy (IfW), 2018)
In this paper the authors propose that G20 countries endorse and facilitate the creation of a T20 digital platform for "Accelerating the Jobs of the Future". In a world driven by a new wave of technological change, the platform would revalue the role of think tanks, research institutions and knowledge hubs to move the global agenda in an issue of central importance for the future of society: the creation of the jobs of the future. Building on and complementing existing experiences, the T20 platform would be a digital hub for producing knowledge, informing policies and connecting potential partners to accelerate the jobs of the future, within the context of an increasing integrated global economy. It would also contribute to the development of consensual views among the research community, allowing to discard extreme visions about the jobs of the future, dispelling both overly optimistic visions with no evidence base and unwarranted fears.
Keywords: J01; E24; F66; O30; 330; employment; future; digitalization; technology; industry 4.0; artificial intelligence; skills; inequality; gender gap; G20